Association between two single nucleotide polymorphisms of interleukin‐27 gene and increased cryptorchidism risk. (18th May 2015) - Chen, P.; Pu, Y.; Zhou, B.; Wang, Y.; Tang, T.; Zhang, P.; Zhang, L.
Summary: Growing evidences have suggested the association between interleukin‐27 and cryptorchidism. We aimed to investigate the relationship between IL‐27 polymorphisms and cryptorchidism susceptibility. A total of 519 males were enrolled in a case–control study (150 cases and 369 normal subjects). The variants were discriminated using polymerase chain reaction–restriction fragment length polymorphism methods. The proportions of the major allele for rs153109 and rs17855750 were A and T with frequencies of 0.56 and 0.85 in cases and 0.51 and 0.91 in controls respectively ( P values = 0.002, P value = 0.002). The heterozygous genotype of rs153109 and 17855750 was A/G and T/G with frequencies of 0.62 and 0.25 in cases and 0.39 and 0.17 in controls respectively ( P values <0.001, P values <0.001). The A allele and A/G genotype of rs153109 polymorphisms contribute to increase cryptorchidism susceptibility, and G allele and T/G genotype of rs17855750 also contribute to increase cryptorchidism susceptibility, which implies that these allele and genotypes may be risk factors for the development of cryptorchidism.